INTERPRETATION OF THE IMAGE OF “DEVOTION” WITHIN THE CONCEPTUAL SPHERE OF UZBEK AND ENGLISH LINGUOCULTURES - Mamatqulova Shokhsanam Isroil qizi (Western European Studies, 2025)
his article explores the linguocultural features of the concept of 'devotion' in Uzbek and English. Based on the theory of the conceptual sphere, the lexical, semantic, stylistic and cultural interpretations of the concept are analyzed comparatively. Examples are drawn from proverbs, literary texts, phraseological units, and lexicographic sources. The results indicate that in Uzbek, devotion is largely linked to communal values, while in English it is often connected with individual loyalty and personal aspirations. The article has both theoretical and practical significance in comparative linguistics, translation studies and lexicography.
Keywords: devotion; concept; conceptual sphere